EFFECT OF GIVING BOKASHI COW MANURE AND TEMPE INDUSTRY LIQUID WASTE ON GROWTH AND PRODUCTION OF CORN (Zea mays L.) - Zulkarnain Tanjung, Dicky; Susanti, Rini; Lubis, Efrida; Apdillah, Zaka; Risnawati, Risnawati (Fruitset Sains : Jurnal Pertanian Agroteknologi, 2024)
Corn plants have a positive impact on human life, which can be used as raw material and can be fed to cattle. The purpose of this study is to identify the growth and production responses of the Maize (Zea mays L.) plant due to the delivery of the bokashi of cattle dirt and the liquid waste of the tempe industry. This research was carried out in February 2017 to June 2017 in the People's Farmland of Man Unidirectional Road, Klippa Town Village, Sei Tuan Percut District, Tembung Field. The scheme used is a factorial group random scheme (RAK) with 3 repetitions and consists of 2 factors. The results of the study show that the use of bokashi of cattle dirt gives a real effect on the high observation parameters, leaf length as well as stick weight on corn crops that have been observed and is not real on the observation of the number of leaves, the leaf area, the weight of dry seeds per plot. For use of liquid waste industry tempe gives a tangible influence on the length of leaf parameters at the age of 6 weeks after planting and the stick / plant weight per plot but has no tangible effect on observations of the plant height, leaves number, sheet width, dry seed weight for each plot.